Multidisciplinarity Is Critical to Unlock the Full Potential of Modern Light Microscopy - Weber, Michael; Huisken, Jan (Frontiers in Cell and Developmental Biology, 2021)
Light microscopy has long been indispensable for many biologists as a tool to capture a visual representation of their biological sample. Lately, it has become an increasingly precise and quantitative technique where images are only an intermediate step, with the ultimate goal to extract statistically relevant data. Recent developments in microscope technology make it possible to, for example, image fragile organisms over long periods of time with exceptional resolution and minimal stress. Instead of manually imaging a few cells, scientists now want to automatically record images from hundreds of samples and extract statistically relevant data. However, such efforts require dedicated, reliable, and reproducible hard- and software that is often out of reach for biologists that rely on what microscope vendors have to offer. Multidisciplinary research laboratories are at the forefront of upgrading light microscopy to a quantitative technique, as this process requires experts from multiple fields that normally do not interact on a daily basis. The establishment of reliable microscopy workflows, the integration of 3rd-party hardware into commercial microscopes, or the development of custom microscope hard- and software is best achieved by a diverse group of collaborators, such as engineers, computer scientists, microscopists, and of course biologists. In this perspective, we highlight the impact of modern light microscopy on biological research and how multidisciplinary structures in research laboratories and institutions are a necessity to further develop microscopy technology and make it accessible for biologists.